2023
DOI: 10.1038/s41598-023-34485-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender specific factors contributing to cognitive resilience in APOE ɛ4 positive older adults in a population-based sample

Abstract: Although APOE ɛ4 has been identified as the strongest genetic risk factor for Alzheimer’s Disease, there are some APOE ɛ4 carriers who do not go on to develop Alzheimer’s disease or cognitive impairment. This study aims to investigate factors contributing to this “resilience” separately by gender. Data were drawn from APOE ɛ4 positive participants who were aged 60 + at baseline in the Personality and Total Health Through Life (PATH) Study (N = 341, Women = 46.3%). Participants were categorised into “resilient”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…People affected by chronic stroke often exhibit poor self-esteem, and active participation in rehabilitation can improve self-esteem and QOL 52 . Additionally, self-e cacy plays a crucial role in the rehabilitation and recovery of elderly people affected by chronic stroke because higher levels of self-e cacy are linked to setting and achieving more ambitious self-goals 53 .…”
Section: Discussionmentioning
confidence: 99%
“…People affected by chronic stroke often exhibit poor self-esteem, and active participation in rehabilitation can improve self-esteem and QOL 52 . Additionally, self-e cacy plays a crucial role in the rehabilitation and recovery of elderly people affected by chronic stroke because higher levels of self-e cacy are linked to setting and achieving more ambitious self-goals 53 .…”
Section: Discussionmentioning
confidence: 99%
“…Resilience to cognitive decline and dementia, such as Alzheimer’s disease, may operate differently for men and women. In this Collection, Zheng et al 24 identified factors that were associated with resilience to cognitive decline in APOE ɛ4 carriers (the largest genetic risk factor for late-life dementia). These were increased mild physical activity and being employed for men, and increased mental engagement for women.…”
mentioning
confidence: 99%